2020
DOI: 10.1186/s12199-020-00921-1
|View full text |Cite
|
Sign up to set email alerts
|

Households with unimproved water sources in Ethiopia: spatial variation and point-of-use treatment based on 2016 Demographic and Health Survey

Abstract: Background Improved water sources are not equally available in all geographical regions. Populations dependent on unsafe water sources are recommended to treat their water at point-of-use using adequate methods to reduce associated health problems. In Ethiopia, the spatial distribution of households using unimproved water sources have been incomplete or ignored in most of the studies. Moreover, evidence on the point-of-use water treatment practice of households dependent on such water sources i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…The majority of the included studies were conducted using interviewers to administer questionnaires. Seven studies from the Amhara region [ 19 , 20 , 23 , 33 , 34 , 36 , 38 ]; four studies from the SNNP region [ 28 30 , 32 ]; one study from the Oromia region [ 21 ]; one study from the Benishangul-Gumuz region [ 37 ]; one study from both the Oromia and Harari regions [ 35 ]; and two studies from the all-region [ 22 , 31 ] were used to obtain the pooled HWT practices and associated factors ( Table 1 ) .…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the included studies were conducted using interviewers to administer questionnaires. Seven studies from the Amhara region [ 19 , 20 , 23 , 33 , 34 , 36 , 38 ]; four studies from the SNNP region [ 28 30 , 32 ]; one study from the Oromia region [ 21 ]; one study from the Benishangul-Gumuz region [ 37 ]; one study from both the Oromia and Harari regions [ 35 ]; and two studies from the all-region [ 22 , 31 ] were used to obtain the pooled HWT practices and associated factors ( Table 1 ) .…”
Section: Resultsmentioning
confidence: 99%
“…A study [ 22 ] revealed an apparent clustering trend of unimproved water coverage between regions. Similarly, in the current study, a spatial clustering was found to be significant in some areas.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, identifying highly vulnerable areas is essential in reducing the lack of improved water sources. Results of a few studies conducted in different settings of Ethiopia revealed that an unimproved source of drinking water was significantly clustered spatially [ 4 , 21 , 22 ]. However, the temporal pattern of unimproved drinking water sources was not incorporated in these studies and they used only one cross-sectional data; it may be unable to analyze the data in time and space domains [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The visual exploration of the distribution of the five groups suggests a clear segmentation of the city into areas with three different levels of consumption: areas with low, medium, and high levels of water consumption. [45][46][47][48][49]…”
Section: Spatial Variation Of Water Consumption In Households Classif...mentioning
confidence: 99%
“…These factors configure a valuable tool for decision-makers and an important basis for formulating efficient water policies. 36,45,46 In this context, this study aims to investigate whether inequality in water consumption among households is characterized by a spatial distribution pattern. It is of particular interest to identify the georeferenced variable that significantly explains the formation of the spatial pattern, as well as working with updated information so that the results make it possible to identify spatial information from which meet pressing water needs for vulnerable groups.…”
Section: Introductionmentioning
confidence: 99%